Dressing, seducing and signifying : from the symbolic dimension of fashion to the contemporary erotic imagery - Oliveira, Madalena (2013)
As a relatively recent social and cultural phenomenon, fashion currently embodies a certain erotic imagery that seems to organise collective life. According to Lipovetsky, it governs our societies. Fashion, being ephemeral by nature, actually expresses the sovereignty of appearance and the power of aesthetic fantasy. It is, in fact, the most significant representation of the triumph of seduction and spectacle. Consequently, fashion is, somehow, a way of understanding the social. This essay builds upon the reasoning of fashion as a mechanism, on the one hand, and as a sign of our times, on the other, to explore how it is the harbinger of a sociality based on the sensitive, unstable and effervescent side of our interpersonal relations with each other and our relationship with the world and things.